MEK inhibitor cobimetinib increases calreticulin and induces immune modulation in TNBC - Ling-Ming Tseng; Ka-Yi Lau; Ji-Lin Chen; Pei-Yi Chu; Chun-Teng Huang; Wan-Lun Wang; Yuan-Ya Chang; Jiun-I Lai; Chi-Cheng Huang; Ming-Shen Dai; Chun-Yu Liu (Journal of Molecular Medicine, 2026)
Immunogenic cell death (ICD) can activate immune cells and potentiate the response to immunotherapy. The mitogen-activated protein kinase (MAPK) signaling pathway regulates the immune response and mediates T-cell receptor signaling. Activation of the MAPK signaling pathway decreases the levels of tumor-infiltrating lymphocytes in triple-negative breast cancer (TNBC) and is associated with worse survival. Here, we investigated the potential of the MEK inhibitor cobimetinib as an ICD inducer in TNBC. We demonstrated that cobimetinib elicited hallmarks of ICD, including elevated levels of damage-associated molecular patterns. Ectopic ERK expression attenuated cobimetinib-induced CRT. Cobimetinib also evoked caspase-8 activation with increased Bax and Bak expression, while caspase inhibitor suppressed cobimetinib-induced CRT expression and apoptosis. In immunocompetent (BALB/c) mice bearing 4T1 tumors, cobimetinib exhibited stronger tumor growth inhibition than in immunodeficient (nude) mice, suggesting an immune-dependent antitumor effect. Furthermore, cobimetinib treatment increased the proportions of naïve CD8 + T cells and effector CD4 + T cells and decreases the proportion of myeloid-derived suppressor cells in immunocompetent mice bearing 4T1 tumors. Notably, we observed differential immunomodulatory effects of cobimetinib in tumor-bearing mice compared to non–tumor-bearing immunocompetent mice. Our findings indicate that MEK inhibition is associated with ICD-related molecular alterations, and that cobimetinib may contribute to immune modulation in TNBC.

Multiplexed EDL-FET biosensor with tannic acid stabilization for simultaneous p-Tau217 and Aβ42/Aβ40 detection in plasma and whole blood from stroke patients - Shang-Chi Chien; I-Yin Chang; Yong-Chuan Chen; Yi-Zhen Lai; Yu-Fang Chen; Pei-Lun Sun; Bor-Ran Li; Yu-Lin Wang; Jung-Chih Chen (Analytica Chimica Acta, 2026)

Early-stage targeted low-dose chlorine-bentonite treatment for cyanobacterial bloom control in deep reservoirs - Xi Li; Shengda Wang; Weijun Song; Bastiaan W. Ibelings; Yiruo Xia; Miquel Lürling; Nesrine Imene Hame; Hichem Nasri; Viktor A. Gabyshev; Andrey Yu. Krasnopeev; Olga I. Belykh; Na Lin; et al. (Journal of Hazardous Materials, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Upscaling Shock Wave Electrodialysis for Scalable Deionization - Yu-I Lin; Po-Chih Tseng; Hyunook Kim; Yupo J Lin; Shu-Yuan Pan (Water Research, 2026)

FBG-based dynamic characterization of a scaled offshore wind turbine foundation model under impact and recorded seismic excitations - Jui-Chi Lin; Yi-Lun Liao; Bor-Yann Chen; I-Hsin Chiu; Wan-Yu Xu; You-Chen Liao; Yi-Heng Yang; Yu-Hsi Huang (Ocean Engineering, 2026)

Invisible plastic release from overlooked usage practices in microwaved food packaging - Pei-Ying Lin; Shu-Ling Hsieh; I-Hsuan Wu; Yu-Chi Hsieh; Shuchen Hsieh (Food Chemistry, 2026)

Microbial-derived metabolites coordinate growth regulation and stress tolerance in Phalaenopsis orchids - Nur Izzatul Maulidah; I-Hung Lin; Yun-Teng Yen; Ting-Yu Liou; Huey-wen Chuang (Journal of Plant Physiology, 2026)

Erratum to “Plant growth–promoting bacteria reshape rhizosphere microecology to regulate Cd, Pb, and Zn mobilization at root–soil interface” [Bioresour. Technol. 451 (2026) 134559] - Caixing Lai; Kaiyang Ying; Xusheng Jiang; Xuehong Zhang; Hongwei Yu; Huachun Lan; Gang Liu; Geoffrey I. Sunahara; Jie Liu; Hua Lin; Yi Li; Guo Yu (Bioresource Technology, 2026)

Plant growth–promoting bacteria reshape rhizosphere microecology to regulate Cd, Pb, and Zn mobilization at root–soil interface - Caixing Lai; Kaiyang Ying; Xusheng Jiang; Xuehong Zhang; Hongwei Yu; Huachun Lan; Gang Liu; Geoffrey I. Sunahara; Jie Liu; Hua Lin; Yi Li; Guo Yu (Bioresource Technology, 2026)

Lactate acts as a metabolic brake on inflammation by repressing NLRP3 transcription via NF-κB inhibition - Hsin-An Lin; Hsin-Chung Lin; Chih-Yung Chiou; Hao-Hsuan Peng; Yu-Jen Chen; Bo-Ying Bao; Kuen-Jou Tsai; Chao-Feng Lin; Chieh-Tien Shih; Sheng-I. Hu; Kuo-Yang Huang; Lih-Chyang Chen (Inflammation Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Dynamic electronic and spin-state modulations of ternary single-atom catalysts for ultrahigh power density and ultra-stable rechargeable zinc-air batteries - Yu-Chieh Ting; Shao-I Chang; Kai-An Lee; Chiung-Wen Chang; Tzu-Hsiang Lin; Chih-Heng Lee; Hsin-Yi Tiffany Chen; Shih-Yuan Lu (Chemical Engineering Journal, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Reductant-driven structural evolution of zinc manganese oxide integrated beta-cyclodextrin for high-performance heavy metal detection - Monica Subramanian; Nandini Nataraj; I.-Hsuan Tung; Yu-Chien Lin; Cihun-Siyong Gong; Hsu-Wei Fang; Ren-Jei Chung (Process Safety and Environmental Protection, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Advancing water and resource recovery from brackish water through electrodialysis-based technologies for circular product ecosystems - Shu-Yuan Pan; Jeremiah Mulia Gianto; Yu-I Lin; Hau-Ming Chang (Desalination, 2026)

Additive-mediated controlled growth of printed perovskite for planar and heterostructure solar cells - Anjali Thakran; Yen-Yu Wang; Rohan Paste; Atul Dhage; Yu-Te Chen; Mario Hofmann; Yu-Jung Lu; Chung Hsin Lu; Shih- I. Lu; Yan-Duo Lin; Chih Wei Chu (Chemical Engineering Journal, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Evaluating hygroscopic cloud-seeding effects by in-situ observation and real-case simulation - Kai-I Lin; Sheng-Hsiang Wang; Kao-Shen Chung; Pay-Liam Lin; Yu-Chieng Liou; Yi-Hui Chang; Yu-Chih Huang; Lin Yi-Sheng (Atmospheric Research, 2026)

Harnessing pyroptosis to restrain melanoma through aripiprazole - Yu-Teng Chang; I-Hsiang Lin; Jeng-Jer Shieh; Tsuo-Hung Lan; Jia-Ning Syu; Shiau-Shian Huang; Po-Hsun Hou (Apoptosis, 2026)

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Detection of Marteilioides chungmuensis in cultured Portuguese oyster (Crassostrea angulata) in southern Taiwan - I-wen Chen; Chieh-Hao Wu; Yi-Pin Lu; Yu-Ju Lin (Fish & Shellfish Immunology, 2025)

Exploring the anticancer potential of Polygonum barbatum (L.) against colorectal cancer: In vitro and in vivo investigations - Pi-Kai Chang; I-Chuan Yen; Wei-Cheng Tsai; Kuen-Tze Lin; Shih-Yu Lee (Phytochemistry Letters, 2025)

Molecular screening of wild and cultivated tomato germplasm reveals potential materials for multi-locus disease resistance breeding - Ehtisham Hussain; Chien-yu Cheng; I-min Huang; Chen-yu Lin; Samrin Gul; Ijaz Rasool Noorka; Assaf Eybishitz; Chutchamas Kanchana-udomkan; Maarten van Zonneveld; Ya-ping Lin (Genetic Resources and Crop Evolution, 2025)

Corrigendum to “Active and intelligent gellan gum-based packaging films for controlling anthocyanins release and monitoring food freshness” [Carbohydrate Polymers 254 (2021) 117410] - Li-Ting Wu; I-Lin Tsai; Yi-Cheng Ho; Yu-Hao Hang; Chi Lin; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2025)

Ionically conductive materials for energy-efficient succinic acid recovery towards electrified circular bioeconomy - Shu-Yuan Pan; Yu-Lun Liao; Yu-I Lin; Po-Chih Tseng (Bioresource Technology, 2025)

Challenges and opportunities in using biowaste for sustainable hydroponic netted melon (Cucumis melo L.) cultivation - Yen-Tzu Fan; Zih-Ee Lin; Pei-Te Chiueh; Yu-Pin Lin; Lien-Chieh Cheng; Yu-Shen Cheng; Shu-I Lin; Chihhao Fan (Agricultural Systems, 2025)

Unraveling the potential of chemical recycling for poly(methyl methacrylate) through pyrolysis: Rigorous modeling, economic, and environmental evaluation - Hsu-Cheng Hua; Meng-Wei Lin; Zi-Cheng Su; I-Lung Chien; Bor-Yih Yu (Process Safety and Environmental Protection, 2025)

Building with nature: Morphological spatial pattern of green infrastructure in urban heat mitigation - Bau-Show Lin; Yu-Hua Tsai; Han-Chin Chang; Chin-Chung Yu; Cheng-I Hsieh (Building and Environment, 2025)

3D printed microtissue cassettes enabling high throughput proton radiobiological assays - Chih-Tsung Yang; I-Chun Cho; Ching-Fang Yu; Edward Cheah; Tesi Liu; Yi-Ping Lin; Sing-Yu Hu; Jyun-Wei Jheng; Ivan Kempson; Tsi-Chian Chao; Sen-Hao Lee; Eva Bezak; et al. (Analytica Chimica Acta, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Single-step pyrolytic synthesis of ultra-microporous ammonialized biochar for carbon dioxide capture - Che-Jung Hsu; I-Lin Kuo; Hsing-Cheng Hsi; Su Shiung Lam; Ying-Pin Huang; Yu-Chieh Ting (Journal of Environmental Management, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

World's largest oligotrophic Lake Baikal: Concerns about cyanobacterial blooms and potential microcystin producers along the littoral zone - Xi Li; Irina V. Tikhonova; Sergey A. Potapov; Andrey Yu. Krasnopeev; Natalya A. Zhuchenko; Xin Niao; Lin Wang; Ekaterina G. Sorokovikova; Weixuan Wang; Olga I. Belykh (Harmful Algae, 2025)

Artificial digestion represents the worst-case scenario for studying nanoplastic fate in gastrointestinal tract - Giselle Lee; Ya-Jhu Jhang; Yu-Tung Jhang; Yen-Chen Chang; Hui-Wen Chang; Chun-Yu Chuang; Yung-Kun Chuang; Ching-Wei Lin; I-Lun Hsiao (Journal of Hazardous Materials, 2025)

In vitro and in silico studies on α-glucosidase inhibitory properties of bioactive components from the rhizomes of Alpinia officinarum Hance - Zakhele Mphatsi Dlamini; Bongani Sicelo Dlamini; Shih-Han Fu; Ya-Lin Chang; Chi-Chien Lin; Yu-Kuo Chen; Kok-Tong Tan; Chi-I Chang (Medicinal Chemistry Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Root exudate-driven rhizospheric recruitment of plant growth-promoting rhizobacteria - Hua LIN; Caixing LAI; Guo YU; Geoffrey I. SUNAHARA; Liheng LIU; Habib ULLAH; Jie LIU (Pedosphere, 2025)

Sulfur-functionalized sawdust biochar for enhanced cadmium adsorption and environmental remediation: A multidisciplinary approach and density functional theory insights - M.M.M. Ahmed; Chih-Hao Liao; S. Venkatesan; Yu-Ting Liu; Yu-Min Tzou; Shih-Hao Jien; Ming-Chang Lin; Yi-Cheng Hsieh; Ahmed I. Osman (Journal of Environmental Management, 2025)

Dual functionality of carbazole-based phosphonic acid molecular additives realizes efficient hole transport layer-free perovskite light-emitting diodes - Yin-Ti Lai; Chiung-Han Chen; Ming-Hsuan Yu; Hsing-Yu Kuo; I-Chih Ni; Bi-Hsuan Lin; Hobeom Kim; Chi-Ching Kuo; Yu-Jung Lu; Chu-Chen Chueh (Chemical Engineering Journal, 2025)

Single-cell atlases reveal leaf cell-type-specific regulation of metal transporters in the hyperaccumulator Sedum alfredii under cadmium stress - Guo Yu; Jingyu Xiang; Jie Liu; Xuehong Zhang; Hua Lin; Geoffrey I. Sunahara; Hongwei Yu; Pingping Jiang; Huachun Lan; Jiuhui Qu (Journal of Hazardous Materials, 2024)

Performance evaluation of resin wafer electrodeionization for enhanced nitrogen recovery from ammonium-containing water environment - Redae Nuguse Berhe; Yu-I Lin; Shu-Yuan Pan; Min Zhan; Hyunook Kim (Chemical Engineering Journal, 2024)

The association of air pollution with blood pressure, heart rate and stress among office workers using essential oils - Chien-Yu Lee; I-Jung Liu; Chih-Hong Pan; Lian-Yu Lin; Hsiao-Chi Chuang; Kin-Fai Ho; Chia-Huang Chang; Kai-Jen Chuang (Atmospheric Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

An integrated approach to optimizing concentration shock wave electrodialysis using 2D multicell simulation and response surface models - Yu-I Lin; Shu-Yuan Pan; Yupo J. Lin; Po-Chih Tseng (Chemical Engineering Journal, 2024)

Photocatalytic reduction of carbon dioxide by BiTeX (X = Cl, Br, I) under visible-light irradiation - Yu-Yun Lin; Fu-Yu Liu; I-Chia Chen; Hwei-Yan Tsai; Jhen-Wei Huang; Jia-Hao Lin; Chiing-Chang Chen (Journal of Environmental Management, 2024)

Kaguacidine A: a novel spirohydantoin-containing cucurbitane glycoside from vines of Momordica charantia L. - Hung-Tse Huang; I-Wen Lo; Yu-Chi Lin; Liao Geng-You; Yun-Sheng Lin; Li-Jie Zhang; Tsung-Lin Li; Chia-Ching Liaw; Yao-Haur Kuo (Natural Product Research, 2024)

Electroneutralization desalination with spontaneous chemoelectric power generation - Aishwarya Rani; Shu-Yuan Pan; Suraj Negi; Yu-I Lin (Water Research, 2024)

CuO NWs boosted triboelectric microfluidic nanosensor functionalized by collagen-protein interactions for real-time platelet count monitoring - Jia-Cheng Lin; Kuldeep Kaswan; Subhodeep Chatterjee; Yu-Wen Wu; Manish Kumar Sharma; Ashok Ranjan; Snigdha Roy Barman; Yu-Zih Lin; Thierry Burnouf; Wilfrid Boireau; Ming-Yen Lu; Yong-Kwang Tu; et al. (Chemical Engineering Journal, 2024)

Life cycle assessment and techno-economic analysis of sustainable bioenergy production: a review - Ahmed I. Osman; Bingbing Fang; Yubing Zhang; Yunfei Liu; Jiacheng Yu; Mohamed Farghali; Ahmed K. Rashwan; Zhonghao Chen; Lin Chen; Ikko Ihara; David W. Rooney; Pow-Seng Yap (Environmental Chemistry Letters, 2024)
The global expansion of the bioenergy industry raises concerns, emphasizing the need for careful evaluation and sustainable management. To facilitate this, life cycle assessments beyond greenhouse gas emissions and energy balance are essential, along with the standardization of assessment methodologies to enable meaningful comparisons. Here, we review life cycle assessment, chemical aspects, and policy implication of bioenergy production. We discuss life cycle assessment in terms of concepts, methods, impacts, greenhouse gases, land use, water consumption, bioethanol, biodiesel, biogas, and techno-economic analysis. Chemical aspects comprise reaction processes and means to improve efficiency. Concerning policies, tools, and frameworks that encourage sustainable energy production are presented. We found that carbon dioxide removal ranges from 45 to 99% in various bioenergy processes. The review also emphasizes the importance of chemistry in advancing sustainable bioenergy production for a more sustainable and secure energy future.

The SMAC mimetic GDC-0152 is a direct ABCB1-ATPase activity modulator and BIRC5 expression suppressor in cancer cells - I-Li Lin; Yu-Ting Lin; Yung-Chieh Chang; Sree Karani Kondapuram; Kai-Hsuan Lin; Pin-Chen Chen; Chung-Ying Kuo; Mohane Selvaraj Coumar; Chun Hei Antonio Cheung (Toxicology and Applied Pharmacology, 2024)

Long-term phytoextraction potential and mechanism of Celosia argentea on soils with different levels of Cd and Mn co-contamination - Guo Yu; Habib Ullah; Hua Lin; Geoffrey I. Sunahara; Xuehong Zhang; Baoliang Chen; Hongwei Yu; Asfandyar Shahab; Liheng Liu; Jie Liu (Journal of Environmental Chemical Engineering, 2024)

Agar-altered foaming bacterial cellulose with carvacrol for active food packaging applications - Anita Chandra Kusuma; Yu-Chieh Chou; Chen-Che Hsieh; Shella Permatasari Santoso; Alchris Woo Go; Hong-Ting Victor Lin; I.-Lun Hsiao; Shin-Ping Lin (Food Packaging and Shelf Life, 2024)

Photo-protection and photo-inhibition during light induction in Barbula indica and Conocephalum conicum under different light gradients - Chung-I. Chen; Kuan-Hung Lin; Meng-Yuan Huang; Kuei-Yu Yao; Chau-Ching Huang; Tzu-Chao Lin; En-Liang Chu; Jia-Dong Yang; Ching-Wen Wang (Photosynthesis Research, 2024)

Spatiotemporal variation and inter-transport of atmospheric speciated mercury between Kaohsiung Harbor and neighboring urban areas - I-Chieh Tu; Chung-Shin Yuan; Yu-Lun Tseng; Chia-Wei Lee; Chitsan Lin (Environmental Pollution, 2024)

Polyhydroxyalkanoates bioproduction from bench to industry: Thirty years of development towards sustainability - Priskila Adjani Diankristanti; Yu-Chieh Lin; Ying-Chen Yi; I-Son Ng (Bioresource Technology, 2024)

Associations between paraben exposure, thyroid capacity, homeostasis and pituitary thyrotropic function in the general Taiwanese: Taiwan Environmental Survey for Toxicants (TEST) 2013 - Po-Chin Huang; Hsin-Chang Chen; Shih-Hao Leung; Yu-Jung Lin; Han-Bin Huang; Wan-Ting Chang; Hsin-I. Huang; Jung-Wei Chang (Environmental Science and Pollution Research, 2023)

Electroneutralization with simultaneous highly-efficient desalination exemplified by acidic brackish wastewater - Yu-I Lin; Shu-Yuan Pan (Chemical Engineering Journal, 2023)

Enhanced biomethane production with a low carbon footprint via anaerobic co-digestion of swine wastewater with rice husk - Hung-Cheng Lin; Shu-Yuan Pan; Yu-I Lin; Dan-Thanh Ngoc Cao (Science of The Total Environment, 2023)

Dynamic total factors’ environmental efficiency in European union countries - Ching-Cheng Lu; Yung-ho Chiu; I-Fang Lin; Tai-Yu Lin (Environment, Development and Sustainability, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

High-resolution imaging of O2 dynamics and metal solubilization in the rhizosphere of the hyperaccumulator Leersia hexandra Swartz - Yao He; Na Ding; Guo Yu; Geoffrey I. Sunahara; Hua Lin; Xuehong Zhang; Habib Ullah; Jie Liu (Journal of Hazardous Materials, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

Monitoring ambient air pollution and pulmonary function in asthmatic children by mobile applications in COVID-19 pandemic - Pei-Yu Lin; Jiu-Yao Wang; Bing-Fang Hwang; Ruby Pawankar; I-Jen Wang (International Journal of Hygiene and Environmental Health, 2023)

Evaluation of a subtropical maize-rice rotation system maintained under long-term fertilizer inputs for sustainable intensification of agriculture - Asif Hameed; Yu-Pei Chen; Fo-Ting Shen; Shih-Yao Lin; Hsin-I Huang; Yu-Wen Lin; Chiu-Chung Young (Applied Soil Ecology, 2023)

Integrated transcriptome and metabolome analysis reveals the mechanism of tolerance to manganese and cadmium toxicity in the Mn/Cd hyperaccumulator Celosia argentea Linn - Guo Yu; Habib Ullah; Xinshuai Wang; Jie Liu; Baoliang Chen; Pingping Jiang; Hua Lin; Geoffrey I. Sunahara; Shaohong You; Xuehong Zhang; Asfandyar Shahab (Journal of Hazardous Materials, 2023)

Effect of species, muscle location, food processing and refrigerated storage on the fish allergens, tropomyosin and parvalbumin - Chia-Lin Tsai; Kristy Perng; Yu-Chen Hou; Cheng-Jou Shen; I-Ning Chen; Yi-Tien Chen (Food Chemistry, 2023)

Impacts of 2 and 4°C global warmings on extreme temperatures in Taiwan - I‐Chun Tsai; Pei‐Rong Hsieh; Chao‐Tzuen Cheng; Yu‐Shiang Tung; Lee‐Yaw Lin; Huang‐Hsiung Hsu (International Journal of Climatology, 2023)
Extreme temperatures were considered natural hazards because they could increase morbidity and mortality. Understanding the extreme temperature changes at different warming levels is crucial to climate change mitigation and adoption for human health. This study projected climate change effects on the intensity, occurrence, and duration of extreme temperatures in Taiwan with 2 and 4°C global warming scenarios using the Weather Research and Forecasting model. The future climate simulations were conducted with the pseudo‐global warming approach, and the future climate changes were obtained from the ensemble mean of simulations in the Coupled Model Intercomparison Project 5. The simulated daily mean temperature increased by 1.40 and 3.09°C under 2 and 4°C global warmings. In a warming world, the daily maximum temperature was projected to increase by 1.35–3.00°C, whereas the daily minimum temperature was even higher, leading to weaker diurnal temperature variation in most regions. The simulation results show that intensified heatwaves with frequent and prolonged durations become par for the course, whereas extremely cold days disappear gradually. The occurrence of heatwaves in the future is projected to be five times that in the current climate. Comparing the global warming impacts over different land‐use types, the heatwave occurrence over urban areas rose more quickly than over other land‐use types; forests are less vulnerable to global warming. On the contrary, the changes in extremely cold days over urban areas were weaker than over other land‐use types. Overall, the effects of global warming on temperature revealed that extreme events were more severe with increased temperature than with the mean state of air temperature. Nonlinear behaviours indicated that global warming should be limited to 2°C, and the additional 2°C warming (from 2 to 4°C) should be addressed carefully.

The depth-keeping performance of autonomous underwater vehicle advancing in waves integrating the diving control system with the adaptive fuzzy controller - Yu-Hsien Lin; Chao-Ming Yu; I-Chen Wu; Chia-Yu Wu (Ocean Engineering, 2023)

Two-stage dynamic data envelopment analysis measuring the overall efficiency and productivity changes of industry and agriculture in EU countries - Ching-Cheng Lu; I-Fang Lin; Tai-Yu Lin; Yung-ho Chiu (Journal of Cleaner Production, 2023)

Intelligent films of marine polysaccharides and purple cauliflower extract for food packaging and spoilage monitoring - Han-Lun Huang; I-Lin Tsai; Chi Lin; Yu-Hao Hang; Yi-Cheng Ho; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2023)

Diversity, Distribution, and Density of Marine Mammals Along the Saudi Waters of the Arabian Gulf: Update From a Multi-Method Approach - Lotfi Rabaoui; Ruben H. Roa-Ureta; Lamia Yacoubi; Yu-Jia Lin; Rommel Maneja; Thadickal V. Joydas; Premlal Panickan; Jinoy Gopalan; Ronald Loughland; Perdana K. Prihartato; Ali Qassem; Tyas I. Hikmawan; et al. (Frontiers in Marine Science, 2021)
Despite the important role of marine mammals in marine ecosystems and the imperative for their conservation, there is still a great lack of information on the diversity, distribution, and density of these animals in the Saudi waters of the Arabian Gulf. To fill this gap, an integrative data-collection approach including fishermen’s questionnaires, opportunistic sighting reports, and directed boat-based surveys, was undertaken between 2016 and 2020, leading to the first scientific report of marine mammal diversity, distribution, and density in the region. The results of the different approaches carried out during the study confirmed a high diversity of cetaceans on the west coast of the study area, with bottlenose dolphins ( Tursiops aduncus ), humpback dolphins ( Sousa plumbea ) and dugongs ( Dugong dugon ) as the most common species. While the two dolphin species were found to be widely distributed in both coastal and offshore waters, D. dugon appears to occur exclusively in coastal waters in the southern part of the study area, mainly in the Gulf of Salwah. The presence of both species of dolphins increased during the summer months and in the vicinity of the numerous oil and gas facilities in this region. The distribution of the observed dolphins was found mostly within a 10–20 km radius around each facility. Other cetacean species observed less frequently in the area include Bryde’s whale ( Balaenoptera edeni ), killer whale ( Orcinus orca ), common dolphin ( Delphinus delphis ) and finless porpoise ( Neophocaena phocaenoides ). Regarding the density of marine mammals in the region, boat-based surveys confirmed the results of fishermen’s questionnaires and reports of opportunistic sightings, with bottlenose and humpback dolphins being the most abundant species. These results provide a baseline for policies oriented to the conservation of mammals in the Saudi waters of the Arabian Gulf.

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

New secondary metabolite with cytotoxicity from spawning soft coral Asterospicularia laurae in Taiwan - Jui-Hsin Su; Chih-I Liu; Mei-Chin Lu; Chi-I Chang; Min-Ying Hsieh; Yu-Chi Lin; Chang-Feng Dai; Ya-Han Zhang; Zheng-Yu Lin; Yun-Sheng Lin (Natural Product Research, 2021)

Concurrent increases in post-pacing action potential duration and contractility predict occurrence of ventricular arrhythmia - Chih-Min Liu; Feng-Zhi Lin; Yao-Chang Chen; Yung-Kuo Lin; Yen-Yu Lu; Cheng-I Wu; Satoshi Higa; Shih-Ann Chen; Yi-Jen Chen (Pflügers Archiv - European Journal of Physiology, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

(–)-β-Homoarginine anhydride, a new antioxidant and tyrosinase inhibitor, and further active components from Trichosanthes truncata - I-Ting Weng; Yen-An Lin; Guan-Yu Chen; Hsiu-Mei Chiang; Yi-Jung Liu; Chao-Jung Chen; Yu-Hsuan Lan; Chia-Lin Lee (Natural Product Research, 2020)

Hispidulin Inhibits Neuroinflammation in Lipopolysaccharide-Activated BV2 Microglia and Attenuates the Activation of Akt, NF-κB, and STAT3 Pathway - Chung-I Yu; Cheng-I Cheng; Ya-Fei Kang; Po-Chih Chang; In-Pin Lin; Yu-His Kuo; An-Jie Jhou; Mei-Ying Lin; Chung-Yi Chen; Chien-Hsing Lee (Neurotoxicity Research, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Correction to: Computer vision–based sensors for the tilt monitoring of an underground structure in a landslide area - I-Hui Chen; Yu-Shu Lin; Miau-Bin Su (Landslides, 2020)

Computer vision–based sensors for the tilt monitoring of an underground structure in a landslide area - I-Hui Chen; Yu-Shu Lin; Miau-Bin Su (Landslides, 2020)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Real-Time Water-Level Forecasting Using Dilated Causal Convolutional Neural Networks - Jhih-Huang Wang; Gwo-Fong Lin; Ming-Jui Chang; I-Hang Huang; Yu-Ren Chen (Water Resources Management, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Slope deformation monitoring in the Jiufenershan landslide using time domain reflectometry technology - Shei-Chen Ho; I-Hui Chen; Yu-Shu Lin; Jun-Yang Chen; Miau-Bin Su (Landslides, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Gender differences and lung cancer risk in occupational chefs: analyzing more than 350,000 chefs in Taiwan, 1984–2011 - Pei-Chen Lin; Chiung-Yu Peng; Chih-Hong Pan; Pi-I Debby Lin; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2019)

NTF3 Is a Novel Target Gene of the Transcription Factor POU3F2 and Is Required for Neuronal Differentiation - Yi-Mei J. Lin; I-Lun Hsin; H. Sunny Sun; Shankung Lin; Yen-Ling Lai; Hsuan-Ying Chen; Ting-Yu Chen; Ya-Ping Chen; Yi-Ting Shen; Hung-Ming Wu (Molecular Neurobiology, 2018)

A Comparative Placebo-Controlled Clinical Trial of the Efficacy and Safety of Interferon β-1a Formulations for S.C. Administration in Patients with Remitting Multiple Sclerosis: First-Year Results - A. N. Boiko; L. P. Bosenko; V. V. Vasilovskii; L. I. Volkova; M. N. Zakharova; S. V. Kotov; E. V. Lekomtseva; T. I. Negrich; E. V. Parshina; O. P. Patrusheva; S. V. Prokopenko; D. V. Sazonov; et al. (Neuroscience and Behavioral Physiology, 2018)

Identification of a mutation in CNNM4 by whole exome sequencing in an Amish family and functional link between CNNM4 and IQCB1 - Sisi Li; Quansheng Xi; Xiaoyu Zhang; Dong Yu; Lin Li; Zhenyang Jiang; Qiuyun Chen; Qing K. Wang; Elias I. Traboulsi (Molecular Genetics and Genomics, 2018)

Prevalence, mechanisms and genetic relatedness of the human pathogenic fungus Aspergillus fumigatus exhibiting resistance to medical azoles in the environment of Taiwan - Hsuan‐Chen Wang; Jui‐Chang Huang; Yong‐Hong Lin; Yu‐Hsin Chen; Ming‐I Hsieh; Pui‐Ching Choi; Hsiu‐Jung Lo; Wei‐Lun Liu; Ching‐Shan Hsu; Hsin‐I Shih; Chi‐Jung Wu; Yee‐Chun Chen (Environmental Microbiology, 2018)
Summary Emerging azole resistance in Aspergillus fumigatus poses a serious threat to human health. This nationwide surveillance study investigated the prevalence and molecular characteristics of azole‐resistant A. fumigatus environmental isolates in Taiwan, an island country with increasing use of azole fungicides. Of the 2760 air and soil samples screened from 2014 to 2016, 451 A. fumigatus isolates were recovered from 266 samples and 34 isolates from 29 samples displayed resistance to medical azoles (itraconazole, voriconazole or posaconazole). The resistance prevalence was 10.9% and 7.5% in A. fumigatus ‐positive samples and isolates respectively. Most (29, 85.3%) azole‐resistant isolates harboured TR 34 /L98H mutations, which were widely distributed, clustered genetically with clinical isolates, and had growth rates that were similar to those of the wild‐type isolates. Microsatellite genotyping revealed both the global spread of the TR 34 /L98H isolates and the occurrence of TR 34 /L98H/S297T/F495I isolates belonging to local microsatellite genotypes. AfuMDR3 and atrF , two efflux transporter genes, were constitutively upregulated in two individual resistant isolates without cyp51A mutations, highlighting their potential roles in azole resistance. These results emphasize the need for periodic environmental surveillance at the molecular level in regions in which azole fungicides are applied, and agricultural fungicide management strategies that generate less selective pressure should be investigated.

Role of LIF Cytokine and CD34 Angiogenesis Marker in Non-Developing Pregnancy - E. S. Popravka; A. S. Dyatlova; N. S. Lin’kova; Yu. S. Krylova; V. O. Polyakova; I. M. Kvetnoi (Bulletin of Experimental Biology and Medicine, 2017)

Groundwater origins and recharge in a well field near Chien-Shih, Shinchu, Taiwan - Pei-Ying Lin; Louis Loung-Yie Tsai; Chung-Ho Wang; Kuei-Wen Chang; Yu-Yen Sheng; I-Tzu Chu; Wang-Ru Lee (Sustainable Water Resources Management, 2017)

Effects of Polypropylene Carbonate/Poly(d,l-lactic) Acid/Tricalcium Phosphate Elastic Composites on Improving Osteoblast Maturation - Hsu-Wei Fang; Wei-Yu Kao; Pei-I Lin; Guang-Wei Chang; Ya-Jung Hung; Ruei-Ming Chen (Annals of Biomedical Engineering, 2015)

Interaction of DRD2TaqI, COMT, and ALDH2 genes associated with bipolar II disorder comorbid with anxiety disorders in Han Chinese in Taiwan - Ming-Chuan Hu; Sheng-Yu Lee; Tzu-Yun Wang; Yun-Hsuan Chang; Shiou-Lan Chen; Shih-Heng Chen; Chun-Hsien Chu; Chen-Lin Wang; I Hui Lee; Po See Chen; Yen Kuang Yang; Ru-Band Lu (Metabolic Brain Disease, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Incense burning at home and the blood lead level of preschoolers in Taiwan - Yaw-Huei Hwang; Yi-Shuan Lin; Chia-Yu Lin; I-Jen Wang (Environmental Science and Pollution Research, 2014)

SLDP: a Novel Protein Related to Caleosin Is Associated with the Endosymbiotic Symbiodinium Lipid Droplets from Euphyllia glabrescens - Buntora Pasaribu; I-Ping Lin; Jason T. C. Tzen; Guang-Yuh Jauh; Tung-Yung Fan; Yu-Min Ju; Jing-O Cheng; Chii-Shiarng Chen; Pei-Luen Jiang (Marine Biotechnology, 2014)

Novel quasi-subgenotype D2 of hepatitis B virus identified in Taiwanese aborigines - Huy Tran; Ming-Lung Yu; Chia-Yen Dai; I-Ling Lin; Ming-Lun Yeh; Wan-Long Chuang; Kenji Abe (Virus Genes, 2014)

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

Cingulum Correlates of Cognitive Functions in Patients with Mild Cognitive Impairment and Early Alzheimer’s Disease: A Diffusion Spectrum Imaging Study - Yi-Cheng Lin; Yao-Chia Shih; Wen-Yih I. Tseng; Yu-Hsiu Chu; Meng-Tien Wu; Ta-Fu Chen; Pei-Fang Tang; Ming-Jang Chiu (Brain Topography, 2014)

Nutrient limitation in Auxenochlorella protothecoides induces qualitative changes of fatty acid and expression of caleosin as a membrane protein associated with oil bodies - Buntora Pasaribu; I-Ping Lin; Chii-Shiarng Chen; Chi-Yu Lu; Pei-Luen Jiang (Biotechnology Letters, 2014)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

Tetrapeptide H-Ala-Glu-Asp-Arg-OH Stimulates Expression of Cytoskeletal and Nuclear Matrix Proteins - V. Kh. Khavinson; N. S. Lin’kova; V. O. Polyakova; I. M. Kvetnoy; V. V. Benberin; M. M. D’yakonov; Yu. S. Titkov (Bulletin of Experimental Biology and Medicine, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Fhl1 as a downstream target of Wnt signaling to promote myogenesis of C2C12 cells - Jing-Yu Lee; I-Chun Chien; Win-Yu Lin; Shao-min Wu; Bo-Huei Wei; Yu-En Lee; Hu-Hui Lee (Molecular and Cellular Biochemistry, 2012)

Availability of dopamine and serotonin transporters in opioid-dependent users—a two-isotope SPECT study - Tzung Lieh Yeh; Kao Chin Chen; Shih-Hsien Lin; I. Hui Lee; Po See Chen; Wei Jen Yao; Sheng-Yu Lee; Yen Kuang Yang; Ru-Band Lu; Mei-Hsiu Liao; Nan-Tsing Chiu (Psychopharmacology, 2012)

Relationship between temperature change and the requirement for a permanent pacemaker implantation in bradyarrhythmias - I-Fan Liu; Shih-Lin Chang; Li-Wei Lo; Yu-Feng Hu; Ta-Chuan Tuan; Chi-Woon Kong; Tsu-Juey Wu; Chern-En Chiang; Shih-Ann Chen; Yenn-Jiang Lin (International Journal of Biometeorology, 2011)

Genetic variation in sex-steroid receptors and synthesizing enzymes and colorectal cancer risk in women - Jennifer Lin; Robert Y. L. Zee; Kuang-Yu Liu; Shumin M. Zhang; I-Min Lee; JoAnn E. Manson; Edward Giovannucci; Julie E. Buring; Nancy R. Cook (Cancer Causes & Control, 2010)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Distribution Of Volatile Organic Compounds In Ambient Air Of Kaohsiung, Taiwan - Yu-Jue Hong; Hueiwang Anna Jeng; Yang-Yen Gau; Chitsan Lin; I-Long Lee (Environmental Monitoring and Assessment, 2006)

Study on construction of cDNA libraries from rat normal liver and regeneration liver with smart technique - Lin Jun-Tang; Wang Cong-Rui; Jogenananda Pramanik; Zhang Hui-Yong; Feng Hui-Gen; Yang Bao-Sheng; L. I. Yu-Chang; Xu Cun-Shuan (Indian Journal of Clinical Biochemistry, 2004)

Ground spider diversity in the Kenting uplifted coral reef forest, Taiwan: a comparison between habitats receiving various disturbances - Yu-Lung Hsieh; Yao-Sung Lin; I-Min Tso (Biodiversity and Conservation, 2003)

Risk of hepatocellular carcinoma and habits of alcohol drinking, betel quid chewing and cigarette smoking: a cohort of 2416 HBsAg-seropositive and 9421 HBsAg-seronegative male residents in Taiwan - Li-Yu Wang; San-Lin You; Sheng-Nan Lu; Hsi-Chang Ho; Mei-Hui Wu; Chien-An Sun; Hwai-I Yang; Chien-Jen Chen (Cancer Causes & Control, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)